Pengaruh Pembelajaran Kontekstual dan Pembelajaran Langsung terhadap Hasil Belajar Ditinjau dari Kemampuan Awal Siswa - Bajora Operasi Simanjuntak; KMS Muhammad Amin Fauzi; Sugilar Sugilar (Mahesa Research Center, 2022)
The research aims to determine whether: (1) there is an effect of contextual learning and direct learning on student learning outcomes, (2) the learning outcomes of students who have high initial abilities are better than those of students with moderate or low initial abilities, and (3)) there is an interaction between the learning model and students' initial abilities on learning outcomes. The research method used is quantitative research methods. This research was conducted at SMP N 2 Padangsidimpuan with a sample of 2 classes, namely class IX-10 with 26 students and class IX - 9 with 28 students. Both classes were given a preliminary ability test and a final test in the form of essay questions. After the research data is obtained, the hypothesis is tested by two-way ANOVA. From the results of the ANOVA calculation, it was concluded that: (1) The direct learning model and the contextual learning model had a significant influence on student learning outcomes, seen from the value of F count = 4.132 > F table = 4.03, (2) The learning outcomes of students who have High initial ability is better than the learning outcomes of students who have moderate or low initial abilities in the curved side space material, seen from the value of F count = 61.634 > F table = 4.03, and (3) there is no interaction between the learning model and the ability The beginning of the student learning outcomes in the curved side space material, seen from the value of F count = 0.052 < F table = 4.03.